Determination of hair iron levels of healthy female high school students with aas in the Pendik District, Istanbul-Turkey - (:unkn) unknown (My University, 2012)
Iron (Fe) is essential for the normal physiological functions as an integrated part of many protein and enzyme systems in various human tissues. Fe nutrition is one of great importance for adequate development, and its deficiency is among the most frequent nutritional deficiency disorders resulting in developmental delay, impaired behavior, diminished intellectual performance, reduced work capacity and decreased resistance to infection. This study was conducted among 60 healthy female high school students aged 16 to 20 in the Pendik District of IstanbulTurkey in order to examine the Fe contents of their hair. The measurements of Fe assessments were done by using atomic absorption spectrometer (Varian AA200 model). The personal data of students including age, location, general state of health, dietary habits, possible use of pharmaceuticals, tobacco, alcohol, coffee, etc. were considered and only hair samples of healthy female students were used as experimental materials. The mean value of Fe in female students' hair was assessed as 27.03 ±1.58 mg/kg. Fe levels of samples were found to be similar or slightly higher than the results of many other investigations around the world. Additionally, Fe values of soil samples from seven different stations were also measured in the Pendik District and no relation between soil and hair Fe levels was found. © by PSP.
Keywords: AAS; Iron; Istanbul; Pendik; Trace elements; Turkey